2015
DOI: 10.3233/jad-142016
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Volume in Older Adults at Risk of Cognitive Decline: The Role of Sleep, Vascular Risk, and Depression

Abstract: Although their contribution is small, lower sleep efficiency, low blood pressure, diabetes, and untreated depression are associated with reduced hippocampal volumes. Studies exploring the impact of early intervention for these risk factors on hippocampal integrity are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 65 publications
1
36
0
Order By: Relevance
“…Hippocampal volume is often linked to performance on memory tasks (Schultz et al, 2015), and has also been consistently demonstrated to change with memory training and intervention (Erickson et al, 2011). Hippocampal volume is also known to decrease with age and in association with MCI, AD and other age-related disorders (Lupien et al, 1998; Elcombe et al, 2015). Given that choline-containing compounds measured with 1 H-MRS are associated with cell-membrane turnover, one might expect corresponding structural changes in the hippocampus as well; however, we did not find a link between hippocampal volume and memory training in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal volume is often linked to performance on memory tasks (Schultz et al, 2015), and has also been consistently demonstrated to change with memory training and intervention (Erickson et al, 2011). Hippocampal volume is also known to decrease with age and in association with MCI, AD and other age-related disorders (Lupien et al, 1998; Elcombe et al, 2015). Given that choline-containing compounds measured with 1 H-MRS are associated with cell-membrane turnover, one might expect corresponding structural changes in the hippocampus as well; however, we did not find a link between hippocampal volume and memory training in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…During AD the hippocampus is one of the first regions of the brain to suffer damage. The mechanism of hippocampal atrophy in AD patients is not entirely clear and may be due to neuronal loss, as well as neurite and synaptic degeneration caused by Aβ, highly phosphorylated tau protein, and neurofibrillary tangles, together with other damage factors such as hypotension, diabetes, hyperlipidemia, epilepsy, stress, and affective disorders (Dhikav and Anand 2012;Roberts et al 2014;Elcombe et al 2015). Accumulated evidence shows that there is a close correlation between hippocampal atrophy and cognitive impairment in patients with AD (Yavuz et al 2007;Dhikav and Anand 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found in schizophrenic patients certain neurochemical lateralisation in the HF in relation to quantity of the glutamate receptors and size of the pyramidal cell synapses [13,40]. Finally, functional or pathophysiological right-left HF asymmetry was noticed in memory processing [9], language acquisition [23], posttraumatic stress disorders [41,48], and cognitive decline of various causes [10].…”
Section: Discussionmentioning
confidence: 99%
“…The HF changes in volume were also seen in patients with cognitive impairment, including those with Alzheimer's disease [1,46]. Reduction in the HF volume was observed in heavy cannabis use, in epilepsy, mild cognitive decline, dementia, major depression, the aged, traumatic brain injury, posttraumatic stress disorder, chronic alcoholism, borderline and antisocial personality disorders, obsessive-compulsive disorder, herpes simplex encephalitis, Parkinson's and Huntington's disease, Down's and Turner's syndrome, cardiac arrest, and Cushing's disease [1,10,14,38,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation